2022
DOI: 10.2215/cjn.09170721
|View full text |Cite|
|
Sign up to set email alerts
|

Use and Outcomes of Induction Therapy in Well-Matched Kidney Transplant Recipients

Abstract: Background and objectivesThe optimal induction treatment in low–immune risk kidney transplant recipients is uncertain. We therefore investigated the use and outcomes of induction immunosuppression in a low-risk cohort of patients who were well matched with their donor at HLA-A, -B, -DR, -DQB1 on the basis of serologic typing.Design, setting, participants, & measurementsOur study was an observational study of first adult kidney-only transplant recipients in the United States recorded by the Organ Procuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, many centers have incorporated IL-2 antagonists in post-transplant immunosuppressive regimens [ 221 ]. Still, the results are unclear as to whether the use of IL-2 receptor antagonists are associated with improved post-transplant outcomes [ 221 , 222 ]. For example, a meta-analysis by Ali et al, demonstrated that IL-2R antibody induction therapy did not improve the rate of rejection or graft survival for renal transplant recipients on tacrolimus maintenance therapy.…”
Section: Regulatory T Cell Therapiesmentioning
confidence: 99%
“…Furthermore, many centers have incorporated IL-2 antagonists in post-transplant immunosuppressive regimens [ 221 ]. Still, the results are unclear as to whether the use of IL-2 receptor antagonists are associated with improved post-transplant outcomes [ 221 , 222 ]. For example, a meta-analysis by Ali et al, demonstrated that IL-2R antibody induction therapy did not improve the rate of rejection or graft survival for renal transplant recipients on tacrolimus maintenance therapy.…”
Section: Regulatory T Cell Therapiesmentioning
confidence: 99%
“…Among these, transplant rejection is a big problem that always threatens kidney recipients (12,13). Therefore, to minimize these vital problems, the kidney recipient and donor should be thoroughly examined from an immunological point of view before the kidney transplant operation (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of CJASN , Evans et al (6) compared outcomes for well-matched recipients who received antibody induction with those of recipients who did not receive induction therapy. They used US Organ Procurement and Transplantation Network data and included adult recipients transplanted between 2010 and 2014.…”
mentioning
confidence: 99%
“…Although the case for induction therapy in well-matched recipients is largely theoretical, the argument against its use has some evidence justification. In this context, the findings of Evans et al (6) highlight the need to risk-stratify patients and consider the balance between reducing the 5% short-term risk of rejection with induction therapy and reducing the long-term risk of infections and malignancies (and higher risk of death) by avoiding induction therapy. However, registry-based retrospective studies can only inform us so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation